Studi Retrospektif Karakteristik Pasien Kista Ovarium di RSUD Kota Bogor Periode 2020-2024 - ANDRIANSYAH, NADIA FAZILA; RUSLIM, WELLY HARTONO (Hang Tuah Medical Journal, 2025)
An ovarian cyst is a fluid-filled sac that develops in the ovary. There are two types of lesions which are neoplastic and non neoplastic. The formation of ovarian cysts is affected by hormonal imbalances during puberty and menopause. The purpose of this study is to know the characteristics of ovarian cyst patients at RSUD Kota Bogor for the 2020-2024 period. This study used a total sampling method. The subjects of the study were patients with the diagnosis of ovarian cysts based on biopsy and resection and histopathological examinations listed in the medical records of Bogor City Hospital. In this study, 122 medical records of patients with the majority of patients were between the ages of 40-49 (30,3%) and dominated by married women (82,8%). The characteristics of ovarian cysts are found to be benign histopathological criteria (86,9%). The most common non neoplastic (53,3%) ovarian cyst found is endometriosis (50,8%). The most common neoplastic (46,7%) ovarian cyst found is benign teratoma (28,1%). The most common characteristics were found in 40–49 years of age, with marital status, benign histopathological criteria where endometriosis cyst and mature teratoma as the dominant non-neoplastic and neoplastic cyst.